Recognizing magnetostratigraphy in overprinted and altered marine sediments: Challenges and solutions from IODP Site U1437. (10th August 2016) - Musgrave, Robert J.; Kars, Myriam
Abstract: Core disturbance, drilling overprints, postdepositional acquisition of remanence, authigenic growth of magnetic iron sulfides, and alteration all contribute challenges to recognizing the primary magnetostratigraphy in marine sediments. We address these issues in a sequence of tuffaceous muds and volcaniclastics at International Ocean Discovery Program Site U1437 and produce the longest continuous magnetic polarity stratigraphy in the history of scientific ocean drilling. Remanence measurements were filtered to remove intervals affected by fluidization, plastic sediment disturbance, and core biscuiting. Drilling overprints are concentrated in the disturbed annulus surrounding intact core material. Bioturbation was limited to a vertical extent of at most 15 cm. Changes in sediment color, stiffness, and magnetic hysteresis all suggest that remanence was locked in within a few meters of the sediment–water interface. We did not observe any systematic offset between magnetostratigraphic and biostratigraphic datums. Authigenic growth of greigite, in response to both initial sulfate reduction in the upper 50 m of the sediment column and to deeper resupply of sulfate, has led to magnetic overprinting. Anomalous polarity artefacts, extending <5 m and occurring within about 20 m below a real polarity transition, appear to be due to a chemical remanence acquired by greigite produced during early diagenesis. Diagenetic magnetic mineral alteration resulted in the progressive loss of fine‐grained magnetite, which enhanced susceptibility to drilling and postdrilling overprints and increased the resistance of these overprints to removal by conventional demagnetization. We recovered the magnetostratigraphic record from many samples with resistant overprints through low‐temperature demagnetization through the Verwey transition. Key Points: Site U1437 illustrates techniques for recognizing magnetostratigraphy in altered and overprinted sediments Magnetic sulfide authigenesis produces both normal and reversed polarity artefacts Low temperature demagnetization is effective in removing overprints from MD‐dominated samples